Design and Implementation of an IoT-Based Soilless Aqua-Beans Farm Monitoring System Using Thinker.io - Yukur, Aminu Murtala; Nazif, D. M.; Abdullahi, Nasiru; Nghalmi, S. B. (Darul Yasin Al Sys, 2025)
The increasing global population, coupled with limitations in conventional agriculture—such as land scarcity and water shortages—demands innovative approaches to sustainable food production. Aquaponics, which integrates aquaculture and hydroponics in a closed-loop system, offers a viable solution by recycling water and nutrients. Despite its advantages, traditional aquaponic systems often struggle to maintain optimal environmental conditions and rely heavily on manual oversight. This study presents the design and implementation of a smart, IoT-enabled soilless aqua-beans farm monitoring system, leveraging the Thinker.io platform to address these challenges. The system comprises an ESP32 microcontroller connected to a suite of environmental sensors (temperature, humidity, pH, water level, and light intensity), with data transmitted via MQTT to the Thinker.io cloud for real-time visualization and analysis. An automated feedback mechanism, incorporating water pumps and LED lights, ensures environmental parameters remain within ideal thresholds. A two-day monitoring phase demonstrated the system’s effectiveness in stabilizing conditions necessary for the cultivation of beans and fish. The findings underscore the potential of IoT integration to enhance precision, remote accessibility, and resource efficiency in urban farming. Moreover, the project supports scalability through the provision of documentation and farmer training, aiming to facilitate broader adoption in resource-constrained regions such as Nigeria.